Enhancing stroke response in school children: Efficacy of the HOBIT program - a cluster randomized trial - Ekaterina Volevach; Hana Maršálková; Robert Mikulik (Preventive Medicine Reports)
Objective: Stroke treatment is often hampered by delayed Emergency Medical Services activation. Public campaigns to improve the response to stroke symptoms are either costly or not working. We evaluate the effectiveness of a school-based HOBIT program in improving Emergency Medical Services activation.Methods: This cluster randomized trial was conducted from May to June 2023 at 13 schools in the South Moravian region of Czechia. Schools were randomized to the HOBIT intervention or control group with a 3:1 ratio. Both groups had knowledge assessments at baseline and follow-up. The primary outcome was the percentage change from the pretest to the follow-up test in the intervention group compared to the control group in 4 domains: 1) knowledge, 2) self-efficacy, 3) outcome expectations, 4) behavioral intentions.Results: The baseline knowledge was greater than 50 % in most metrics except for knowledge of the FAST test, which was only 16 %. The intervention effect was 16 % (95 % CI 12–21) for knowledge, 10 % (95 % CI 4–15) for self-efficacy,10 % (95 % CI 5–15) for outcome expectations, 8 % (95 % CI 2–11) for behavioral intentions.Conclusions: In school children, even those with high baseline, “HOBIT” intervention can improve determinants and behavioral intentions of Emergency Medical Services activation for suspected stroke.